Advanced surface engineering materials - Tiwari, Ashutosh; Wang, Rui; Wei, Bingqing (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
Advanced surfaces enriches the high-throughput engineering of physical and chemical phenomenon in relatin to electrical, magnetic, electronics, thermal and optical controls, as well as large surface areas, protective coatings against water loss and excessive gas exchange. A more sophisticated example could be a highly selective surface permeability allowing passive diffusion and selective transport of molecules in the water or gases. The smart surface technology provides an interlayer model which prevents the entry of substances without affecting the properties of neighboring layers. A number of methods have been developed for coatings, which are essential building blocks for the top-down and/or bottom-up design of numerous functional materials. Advanced Surface Engineering Materials offers a detailed up-to-date review chapters on the functional coatings and adhesives, engineering of nanosurfaces, high-tech surface, characterization and new applications. The 13 chapters in this book are divided into 3 parts (Functional coatings and adhesives; Engineering of nanosurfaces; High-tech surface, characterization and new applications) and are all written by worldwide subject matter specialists. The book is written for readers from diverse backgrounds across chemistry, physics, materials science and engineering, medical science, environmental, bio- and nano- technologies and biomedical engineering. It offers a comprehensive view of cutting-edge research on surface engineering materials and their technological importance.
Functional Coatings and Adhesives. Bio-inspired Coatings and Adhesives / Saurabh Das, Saurabh Das, Saurabh Das, B Kollbe Ahn, B Kollbe Ahn -- Advancement of Surface by Applying a Seemingly Simple Sol-gel Oxide Materials / Justyna Krzak, Beata Borak, Anna Lukowiak, Anna Donesz-Sikorska, Bartosz Babiarczuk, Krzysztof Marycz, Anna Szczurek -- Femtosecond Laser Texturing of Bio-based Polymer Films for Surface Functionalization / A Daskalova -- Engineered Electromagnetic Surfaces and Their Applications / Mirko Barbuto, Filiberto Bilotti, Alessio Monti, Davide Ramaccia, Alessandro Toscano -- Structural and Hydroxyapatite-like Surface Functionalization of Advanced Biomimetic Prototype Interface for RA Endoprostheses to Enhance Osteoconduction and Osteointegration / Ryszard Uklejewski, Ryszard Uklejewski, Piotr Rogala, Mariusz Winiecki, Mariusz Winiecki -- Engineering of Nanosurfaces. Biosynthesis of Metal Nanoparticles and Graphene / Ujjal Kumar Sur -- Surface Modifiers for the Generation of Advanced Nanomaterials / Pinar Akkus Sut, Melike Belenli, Ozlem Sen, Melis Emanet, Mine Altunbek, Mustafa Culha -- Nanoassisted Functional Modulation of Enzymes: Concept and Applications / Arka Mukhopadhyay, Hirak K Patra -- Electrospun Fibers Based on Biopolymers / Alicia Mujica-Garcia, Alicia Mujica-Garcia, Agueda Sonseca, Marina P Arrieta, Maysa Yusef, Daniel Lopez, Enrique Gimenez, Jose M Kenny, Jose M Kenny, Laura Peponi -- Nanostructured Materials as Biosensor Transducers: Achievements and Future Developments / NF Starodub, KE Shavanova, NF Shpyrka, MM Melnichenko, RV Viter, RV Viter -- High-tech Surface, Characterisation, and New Applications. Optical Emission Spectroscopy Investigation of Direct Current Micro-plasma for Carbon Structures Growth / Dana-Cristina Toncu -- Advanced Titanium Surfaces and Its Alloys for Orthopedic and Dental Applications Based on Digital SEM Imaging Analysis / Sahar A Fadlallah, Sahar A Fadlallah, Amira S Ashour, Nilanjan Dey -- Deep-blue Organic Light-emitting Diodes: From Fluorophores to Phosphors for High-efficiency Devices / Frederic Dumur -- Plasma-material Interactions Problems and Dust Creation and Re-suspension in Case of Accidents in Nuclear Fusion Plants: A New Challenge for Reactors like ITER and DEMO / A Malizia, LA Poggi, JF Ciparisse, S Talebzadeh, M Gelfusa, A Murari, P Gaudio.
Includes bibliographical references and index.
Print version record.
Keywords: Coatings; Adhesives; Smart materials; Surfaces (Technology); Coating processes; Electronic books